Intergenerational relationships and the life course: changing relations between children and caregivers in Ethiopia - Tafere, Y (Young Lives, 2013)
Drawing on three rounds of survey and qualitative data collected by the Young Lives study in Ethiopia among children born in 1994-95 and their caregivers, this paper investigates intergenerational relationships by means of the life-course perspective. The life-course perspective establishes the importance of understanding intergenerational relationships within changing contexts of time and place. The study shows that parent–child relations are taken for granted when children are young; but as they grow older, parental expectations and filial obligations become explicit. In the context of rapid social change, which sometimes carries risks for children, parents assume that they have an obligation to guide their children. With the expansion of modern education and children’s exposure to different experiences outside the family, many of them contest parental values, norms and expectations. Schooling and other competing agents of ‘socialisation’ have contributed to increased intergenerational conflicts and negotiations. One important outcome of such changes is the transformation of relationships based on traditional processes of socialisation where norms and practices have been simply transmitted across generations, into ‘negotiated’ relationships where children’s agency become increasingly visible. On the other hand, in the context of poverty and social change, children’s key transitions have become more unpredictable. For example, at one and the same age, children could be in school, or in paid work, or married, or having their own child. Such multiple pathways make it difficult for parents to transfer traditional age-based societal norms. The unpredictability and multiplicity of transitions are also major challenges for the life-course perspective as applied to intergenerational relationships. A life-course perspective needs to adapt to such changing circumstances, using the type of longitudinal evidence on which this paper is based.